Prevalence and characteristics of dengue virus co-infection in patients and mosquitoes collected from patients’ houses - Supranee Phanthanawiboon; Tipaya Ekalaksananan; Jureeporn Chuerduangphui; Apiporn Thinkhamrop Suwannatrai; Sirinart Aromseree; Neal Alexander; Hans J. Overgaard; Panwad Thongchai; Ati Burassakarn; Chamsai Pientong (PLoS ONE, 2025)
Co-infection with multiple DENV serotypes can affect human immune status and complicate the clinical presentation and management of dengue patients, so understanding the prevalence and dynamics of co-infection is important for effective dengue control. We aimed to identify and characterize DENV co-infection patterns in field-caught mosquitoes and dengue patients. This study was conducted in northeastern Thailand between June 2016 to August 2019. Female Aedes mosquitos collected from and around dengue patient’s houses were analyzed for DENV infection and presence of serotypes using RT-PCR. DENV serotyping was successful in 154 (39.49%) of human and 165 (14.26%) of mosquito samples. Prevalence of DENV co-infection in patients and mosquitoes was 22.73% (35 cases) and 28.48% (47 samples), respectively. Co-infection with multiple serotypes were double (human 88.57%, mosquito 89.36%), triple (human 5.72%, mosquito 10.64%) and quadruple (human 5.72%, mosquito 0%) infections. Concurrent infection was different between hosts and concurrence patterns of DENV serotype in each host mostly composed of the predominant serotype of the detected year. This is the first report that show DENV co-infection patterns in field-caught mosquito and in dengue fever patients with combinations of triple and quadruple serotypes in Thailand. These finding are potentially useful for understanding shifts in serotypes, concurrent DENV infection patterns, vaccine development, and further research on the ability of vectors to transmit multiple serotypes.